Hesperidin Inhibits Lung Cancer In Vitro and In Vivo Through PinX1 - Yao, Yang; Lin, Mingyue; Liu, Zhujun; Liu, Mengyang; Zhang, Shiheng; Zhang, Yukun (Frontiers in Pharmacology, 2022)
New drug or active lead with high efficiency and low toxicity is needed in the treatment of lung cancer. Natural products are an important source of anti-tumor drugs. At present, there are many molecular-targeted anti-tumor drugs derived from natural products or their derivatives for tumor treatment or in clinical trials. Hesperidin is flavanone isolated from the Rutaceae plant lime Citrus aurantium L. or Citrus sinensis Osbeck. It has been considered to inhibit cancer cell viability in vitro. However, the effect of hesperidin on lung cancer and its underlying mechanism remains unclear. In this study, we found that pinX1 expression level is closely related to overall survival and plays an important role in regulating lung cancer cell proliferation, migration, invasion, and senescence. More importantly, hesperidin significantly increased pinX1 protein expression, and knockdown pinX1 by its specific siRNA blocked the protective effects of hesperidin. Moreover, we also assessed hesperidin at 100 mg/kg is safe in vivo. These findings showed that hesperidin is a potential therapeutic candidate for preventing the progression of lung cancer.